Involvement of miRNAs in Placental Alterations Mediated by Oxidative Stress. (18th March 2014) - Rudov, Alexander; Balduini, Walter; Carloni, Silvia; Perrone, Serafina; Buonocore, Giuseppe; Albertini, Maria Cristina
Abstract : Oxidative stress (OS) is known to be strongly involved in a large number of fetal, neonatal, and adult diseases, including placental disorders, leading to pregnancy loss and stillbirths. A growing body of research links OS to preeclampsia, gestational diabetes, obesity, spontaneous abortion, recurrent pregnancy, preterm labor, and intrauterine growth restriction. While a considerable number of miRNAs have been related to physiological functions and pathological conditions of the placenta, a direct link among these miRNAs, placental functions, and OS is still lacking. This review summarizes data describing the role of miRNAs in placental pathophysiological processes and their possible impact on OS damaging responses. As miRNAs can be found in circulation, improving our understanding on their role in the pathogenesis of pregnancy related disorders could have an important impact on the diagnosis and prognosis of these diseases.